2016
DOI: 10.1002/jsfa.8115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial resistance and quinolone resistance factors in high‐level ciprofloxacin‐resistant Enterococcus faecalis and Enterococcus faecium isolates obtained from fresh produce and fecal samples of patients

Abstract: No significant differences were observed in antimicrobial resistance patterns and genetic characteristics among the isolates from fresh produce and fecal samples. Therefore, good agricultural practices in farming and continuous monitoring of patients, food and the environment for Enterococcus spp. should be performed to prevent antimicrobial resistance and enable reduction of resistance rates. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…These data are similar to previous reports [1,22]. In this study, the rate of ciprofloxacin resistance in Enterococcus species was high and most isolates exhibited high levels of resistance (MIC50=32 mg/L, MIC90=256 mg/L), as reported previously [23]; the rate of ciprofloxacin resistance in E. faecium species showed a significant difference when compared to E. faecalis (84.91% of E. faecium and 63.16% of E. faecalis strains), similar to a previous report [24].…”
Section: Discussionsupporting
confidence: 92%
“…These data are similar to previous reports [1,22]. In this study, the rate of ciprofloxacin resistance in Enterococcus species was high and most isolates exhibited high levels of resistance (MIC50=32 mg/L, MIC90=256 mg/L), as reported previously [23]; the rate of ciprofloxacin resistance in E. faecium species showed a significant difference when compared to E. faecalis (84.91% of E. faecium and 63.16% of E. faecalis strains), similar to a previous report [24].…”
Section: Discussionsupporting
confidence: 92%
“…The type of mutations is also different: In a study conducted by Lopez et al, 15 all strains with ciprofloxacin MIC >32 mg/l presented amino acid changes in GyrA protein (S83I, S83Y, S83R or S83I, and E87G) with/without changes in ParC protein (S80I or S80R or S80I). A report by Kanematsu et al 19 10,20 This is in contrast to Yasufuku et al 16 who found that mutations were significantly correlated with the MICs of levofloxacin.…”
Section: Discussionmentioning
confidence: 79%
“…The SENTRY Antimicrobial Surveillance Program was designed to track antimicrobial resistance trends and the spectrum of microbial pathogens causing human infection on a global scale. The SENTRY Program has unique features that distinguish it from other excellent surveillance projects, such as the SCOPE Program [46, 47], the NHSN [2, 48], the European Antimicrobial Resistance Surveillance Network (EARS-Net) [49], and population-based surveillance programs conducted in the United States [5, 29], Australia [14], Canada [13, 16, 17], China [18], India [15], South Korea [59], Norway [60], and Taiwan [19]. Whereas these cited programs are usually based in a single country, may track only nosocomial infections, and/or rely primarily on a wide variety of susceptibility testing results/methods from participating centers, the SENTRY Program monitors nosocomial and community-onset infections on a global scale using validated reference identification and antimicrobial susceptibility testing methods in a central monitoring laboratory design, including central quality assurance [10, 24, 33, 35–42].…”
Section: Discussionmentioning
confidence: 99%